Cooperative photoredox catalysis. (20th April 2016) - Lang, Xianjun; Zhao, Jincai; Chen, Xiaodong
Abstract : Cooperative photoredox catalysis bridges visible-light photoredox catalysis with other types of catalysis like transition-metal catalysis, biocatalysis or electrocatalysis for establishing demanding organic transformations. Abstract : Visible-light photoredox catalysis has been experiencing a renaissance in response to topical interest in renewable energy and green chemistry. The latest progress in this area indicates that cooperation between photoredox catalysis and other domains of catalysis could provide effective results. Thus, we advance the concept of cooperative photoredox catalysis for organic transformations. It is important to note that this concept can bridge the gap between visible-light photoredox catalysis and other types of redox catalysis such as transition-metal catalysis, biocatalysis or electrocatalysis. In doing so, one can take advantage of the best of both worlds in establishing organic synthesis with visible-light-induced redox reaction as a crucial step.